Comparative Efficacy and Acute Tolerability of a Standardized Withania somnifera Root Extract Versus Sertraline in Generalized Anxiety Disorder: A Randomized, Double-Blind, Placebo-Controlled Non-Inferiority Trial - Ni Made Nova Indriani; Suyong Zhou; Riri Arisanty Syafril Lubis; Jason Willmare (HM Publisher, 2025)
Generalized anxiety disorder (GAD) represents a significant psychiatric burden, characterized by chronic hyperarousal and dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis. While selective serotonin reuptake inhibitors (SSRIs) like Sertraline are the standard of care, their utility is often compromised by delayed onset and adverse effects, specifically sexual dysfunction. Withania somnifera (Ashwagandha) acts as a GABA-mimetic and adaptogen, yet rigorous head-to-head comparisons against pharmaceutical controls are rare. We conducted an 8-week, randomized, double-blind, placebo-controlled trial involving 150 adults with DSM-5 diagnosed GAD. Participants were randomized (1:1:1) to receive High-Concentration Ashwagandha Root Extract (600 mg/day, standardized to >5% withanolides), Sertraline (50 mg/day), or Placebo. Blinding was maintained using mint-scented desiccants to mask the herb's odor. Efficacy was analyzed using Mixed Models for Repeated Measures (MMRM). Of 150 participants, 138 completed the study. Both Ashwagandha (Mean HAM-A reduction -14.2) and Sertraline (-15.1) demonstrated statistical superiority over Placebo (-5.4; p < 0.001). The difference between active arms was not statistically significant, supporting comparable efficacy. Ashwagandha significantly reduced serum cortisol (-24.3%) and improved GAD-7 scores. Crucially, while Sertraline induced significant sexual dysfunction (worsened ASEX scores, p < 0.001) and nausea (28%), Ashwagandha showed a safety profile indistinguishable from placebo. In conclusion, standardized Withania somnifera extract (600 mg/day) offers anxiolytic efficacy comparable to Sertraline (50 mg/day) with a superior safety profile, specifically devoid of sexual and gastrointestinal adverse effects.